Examining the Frequency of Depression in Mothers of Children with Intellectual Disability - Anees, Usama; Saleem, Fiaza; Naeem, Iqra; Ali Bukhari, Syed Rafeh; Jamil, Muhammad Irfan (Indus Journal of Bioscience Research, 2025)
Background: Mothers of children with intellectual disability experience elevated psychological distress compared to the general population. This study aimed to determine the frequency and severity of depression among mothers of children with intellectual disability. Methods: A cross-sectional study was conducted at the Department of Psychiatry, Lahore General Hospital, from August 2024 to January 2025. One hundred mothers of children with intellectual disability aged 4-18 years were enrolled using consecutive sampling. Depression was assessed using Beck’s Depression Inventory, with scores categorized as minimal (0-13), mild (14-19), moderate (20-28), or severe (29-63). Child intellectual disability severity was documented using Wechsler Intelligence Scale scores. Chi-square tests examined associations between demographic variables and depression severity. Results: The mean maternal age was 34.6±7.2 years. Depression was present in 81 mothers (81%), with 19 (19%) showing minimal depression, 24 (24%) mild depression, 32 (32%) moderate depression, and 25 (25%) severe depression. The mean BDI score was 22.4±8.6. Significant associations were found between depression severity and maternal education level (χ²=12.8, p=0.005), with 25 illiterate mothers (78.1%) experiencing moderate to severe depression. Family income showed significant association (χ²=15.3, p=0.002), with 31 mothers (73.8%) from low-income families experiencing moderate to severe depression. Employment status was significantly associated (χ²=8.7, p=0.003), with 50 housewives (64.1%) showing moderate to severe depression. Child-related factors included intellectual disability severity (χ²=18.6, p<0.001) and presence of comorbidities (χ²=11.4, p=0.001), with 46 mothers (68.7%) of children with comorbidities experiencing moderate to severe depression. Conclusions: Depression prevalence among mothers of children with intellectual disability was substantially elevated, with severity linked to child disability characteristics and maternal socioeconomic factors. Comprehensive mental health screening and targeted interventions are essential for this vulnerable population.